Disinfection Byproducts Bind Human Estrogen Receptor‐α. (20th March 2019) - Holmes, Breanne E.; Smeester, Lisa; Fry, Rebecca C.; Weinberg, Howard S.
Abstract: Disinfection byproducts are formed during most drinking water treatment and presently number >800, some of which are implicated in human health outcomes including bladder cancer and infertility, with unknown mechanisms of action. In particular, it is not yet understood whether these compounds can disrupt the estrogen‐signaling pathway through binding to the human estrogen receptor (ER). In the present study, 21 disinfection byproducts, selected for their predicted involvement in endocrine‐related diseases and their structural diversity, were individually evaluated for their binding affinity to the human ER and in silico, and then a subset of these chemicals was studied in binary mixtures with the known weak estrogen, 4‐ n ‐nonylphenol. Individually, 9 of the 21 disinfection byproducts were able to weakly bind to the ER, with affinities ranging from log median inhibitory concentration values of –3.83 to –2.19 M. In binary mixtures, the chemicals followed concentration addition, with their weak binding affinities having little contribution to the overall mixture affinity. These results demonstrate the variety of small‐molecule disinfection byproduct structures that are capable of binding to the ER, and that their weak binding can still be of importance when overall human exposure to mixtures of disinfection byproducts in disinfected drinking water is considered. Environ Toxicol Chem 2019;9999:1–9. © 2019 SETAC Abstract : More than 800 disinfection byproducts have been identified. Among them, some structurally diverse compounds are able to bind to the human estrogen receptor.